Photography and Invisible Borders : Spaces of Imagination between Switzerland and Italy - Grillo, Nicoletta, (Early Modern History and Modern History E-Books Online, Collection 2024, 2024)
Think of national borders beyond just lines: this invitation guides Nicoletta Grillo's journey into the Swiss-Italian border, a journey shaped through the lens of photography theory and practice. Moving between contemporary cross-border work and south-north migrations, this study unveils today's borderscapes as dynamic constellations of spatial practices and imaginations. The book delves into landscape representations by combining the analysis of contemporary photographic artwork with field research and with the author's own photographs, displayed in an extensive photo-textual travelogue. Perspectives from critical border studies, research in the arts, and urban studies come together to offer a larger reflection on the re-imagination of borderscapes.